The Effect of Profitability, Solvency and Market Ratio on Stock Returns (Empirical Study of Food and Beverage Sector Manufacturing Companies Listed on the IDX For the 2019-2023 Period) - Sari, Puspita; Setyadi, Bakti (Journal of Accounting and Finance Management, 2025)
One of the most often used financial market tools is stocks. One option available to the business when choosing how to raise money is to issue shares. Finding out how market ratios, profitability, and solvency affect stock returns is the aim of this study. This study employs a descriptive and quantitative research approach.The study's sample consists of 19 food and beverage manufacturing firms that were listed on the IDX between 2019 and 2023. The results of the study demonstrate that stock returns are influenced by market ratios, profitability, and solvency, and that these impacts happen concurrently.